Peripheral communities of the Eastern Lau Spreading Center and Valu Fa Ridge: community composition, temporal change and comparison to near‐vent communities. (2nd April 2016) - Sen, Arunima; Kim, Stacy; Miller, Alex J.; Hovey, Kyle J.; Hourdez, Stéphane; Luther, George W.; Fisher, Charles R.
Abstract: Western Pacific hydrothermal vents will soon be subjected to deep‐sea mining and peripheral sites are considered the most practical targets. The limited information on community dynamics and temporal change in these communities makes it difficult to anticipate the impact of mining activities and recovery trajectories. We studied community composition of peripheral communities along a cline in hydrothermal chemistry on the Eastern Lau Spreading Center and Valu Fa Ridge (ELSC‐VFR) and also studied patterns of temporal change. Peripheral communities located in the northern vent fields of the ELSC‐VFR are significantly different from those in the southern vent fields. Higher abundances of zoanthids and anemones were found in northern peripheral sites and the symbiont‐containing mussel Bathymodiolus brevior, brisingid seastars and polynoids were only present in the northern peripheral sites. By contrast, certain faunal groups were seen only in the southern peripheral sites, such as lollipop sponges, pycnogonids and ophiuroids. Taxonomic richness of the peripheral communities was similar to that of active vent communities, due to the presence of non‐vent endemic species that balanced the absence of species found in areas of active venting. The communities present at waning active sites resemble those of peripheral sites, indicating that peripheral species can colonize previously active vent sites in addition to settling in the periphery of areas of venting. Growth and mortality were observed in a number of the normally slow‐growing cladorhizid stick sponges, indicating that these animals may exhibit life history strategies in the vicinity of vents that differ from those previously recorded. A novel facultative association between polynoids and anemones is proposed based on their correlated distributions.